Celastrol attenuates diabetic kidney disease progression by repressing senescence of renal tubular epithelial cells - Zhang, Yajun; Sun, Zewei; Meng, Weixue; Lei, Siqi; Sun, Jingyong; Tang, Yixuan; Mu, Xiaodong (Frontiers in Aging, 2025)
BackgroundRecent investigations across both animal models and human cohorts increasingly highlight cellular senescence as a critical pathological process driving the development and progression of diabetic nephropathy (DN). The detrimental impact of senescent cells on DN advancement stems from a range of underlying mechanisms, notably telomere attrition, compromised mitochondrial function, dysregulated autophagy, chronic inflammatory responses, altered mTOR signaling and Sirtuin activity, and the release of pro-coagulant factors. Diabetic kidney disease (DKD) is a common and serious complication in diabetic patients, closely associated with high glucose-induced defects in kidney cells. Currently the clinical treatment of DKD disease is still a challenge. Celastrol, a compound derived from Tripterygium wilfordii, has shown significant therapeutic effects on DKD, but the specific mechanisms remain unclear.MethodsWe established in vitro and in vivo models of DKD using human renal tubular epithelial cells (HK-2) and Sprague-Dawley (SD) rats. The effects of celastrol on glucose-induced oxidative damage to HK-2 cells and kidney injury in DKD rats were observed. The potential mechanisms were investigated through both in vitro and in vivo experiments.ResultsHigh glucose induced accelerated senescence of HK-2 cells in vitro, and celastrol reversed senescence-associated pathological changes in the cells. Celastrol reduced pro-inflammatory signaling and mitochondrial damage in vitro by inhibiting the phosphorylation of aging- and inflammation-related proteins NF-κB and AKT1. In vivo, celastrol inhibited the phosphorylation of NF-κB and AKT1 in renal tissues, effectively improving renal dysfunction and pathological changes in DKD rats, and reducing disease-related indicators.ConclusionCelastrol may be a promising candidate drug for the treatment of DKD. It can treat DKD by reversing the imbalance of the immune-inflammatory system mediated by the AKT/NF-κB/TNF-α signaling during the progression of the disease and may also delay the progression of DKD through its anti-aging effect.